REJECTION OF INSURANCE CLAIMS DUE TO THE INSURED'S DISHONESTY REGARDING THE HISTORY OF ILLNESS - Indra Saputra, Mochamad Kahfi; Simanjuntak, Kornelius (LPSDI Bina Patria, 2023)
This study examines and analyzes the rejection of insurance claims because the insured does not honestly disclose the history of illness he has experienced. The research method used is a normative juridical method with secondary data in the form of insurance legislation, insurance policies, and insurance literature, data analysis is carried out qualitatively. Insurance is an agreement to transfer risk from an insured or policyholder to an insurer or insurance company. The insured or policyholder should pay a certain amount of money as a risk transfer fee called the insurance premium. If there is a risk that has been agreed, the insurer must pay insurance benefits or claims whose amount has been stated in the policy which is referred to as the sum insured. Good faith in the form of honesty in filling out and answering questions at the beginning of the insurance closing process, especially medical history or illness that has been or is being suffered or experienced by the prospective insured is very important because it will have an impact on the claim settlement process. If the prospective insured or insured does not have good faith and does not honestly fill in and answer questions about the history of his health condition, it will have an impact on every claim that occurs and is submitted by the insured becomes not guaranteed by the policy, meaning that the insurer has no obligation to pay claims or policy benefits because the policy becomes null and void or void by itself as stipulated in Article 251 of the KUHD. To avoid disputes, and disappointment with the insured / policyholder in the claim, it is recommended that everyone who wants to buy an insurance policy always have good intentions, namely honestly in submitting data, information, and information about his medical history when filling out and answering questions in the Life Insurance Application Letter (SPAJ) form